International protection of intellectual property rights - Janković Dijana (Međunarodni Problemi, 2013)
The protection of intellectual property rights can be of a great importance for the development of a society. It can contribute to strengthening of the economy and improve the standard of living. The international community has established standards for the protection of intellectual property rights through relevant international documents, thus providing guidelines for the improvement of their international protection. The states which are leaders in innovation and creativity establish strong legal mechanisms that provide the protection of intellectual property rights. It is generally accepted that only the legal use of intellectual property can bring innovation and progress to a society. It is necessary for all sectors, including copyright owners, internet providers and advertising brokers, to cooperate with state prosecutors in order to find practical and efficient solutions for the protection of intellectual property rights. Types of intellectual property infringement are usually manifested through illegal production, smuggling and distribution of counterfeit products, through criminal offences involving money laundering as well as trademark, name and copyright infringement. Criminal investigations are thus focused on identifying, obstructing and disabling international criminal organizations which deal with criminal activities aimed at intellectual property infringement.